Quality Management In Micro Enterprises Food And Beverage Processing Industry - Tan, Juh Hau (Universiti Sains Malaysia, 2017)
Small and Medium Enterprises (SMEs) play important roles in Malaysia’s economy growth. There is a growing trend in the number of micro enterprises in food and beverage processing industries. Many of them are family-based enterprises. It is proven difficult to enlarge the business without a proper quality management system especially to the international market. One of the popular quality tools is Total Quality Management (TQM). It is a continuous improvement approach to improve the performance of a company by improving the processes, products, services, cultures and environments. The implementation of TQM in SMEs’ food and beverage processing industry especially in micro enterprises is still hard due to financial and technical constrains faced by them. In order to overcome these challenges, research on the quality management system practices adopted by these enterprises is conducted. Hence, the critical elements in implementing TQM is identified. Subsequently, the link between TQM elements and organizational performance is found. Study on TQM elements that directly impact the organizational performance will reduce the financial constrains while encouraging more quality activities. A case study was conducted with three micro enterprise food and beverage processing companies in Northern Malaysia area to determine the current practices of quality management system. The determinants of the TQM elements are identified. Structured interview was conducted with the company owner or the general manager to obtain the quality data and information needed for the research. The data was then analysed and interpreted to suits the research objectives. It is found that the current quality management system level is still low for the micro enterprises and the quality practices focus solely on the product. The determinants of TQM elements identified are leadership, supplier focus, customer focus and continuous improvement, and they affects the operational and business performance of the case studies companies. Meanwhile, human resource management and quality assurance affects the innovation performance. Leadership remains the major important element in implementing a quality management system in the company. The implementation of quality management system such as TQM is beneficial and crucial to the growth of the micro enterprises on becoming competitive firms in local and international scenes.